Can AI influencers be ethically designed and implemented? - Toh, Zhongyan (Nanyang Technological University, 2022)
This paper will focus on the ethical aspect of AI influencers and argue that AI influencers can be designed and implemented ethically. The goal of my paper is to argue that AI influencers can replace human social influencers if these AI influencers can perform tasks ordinarily performed by human social influencers and can be ethically designed and implemented. Before my discussion on ethics, I will first briefly argue for the value of human social influencers in society with reference to John Rawls concept of political liberalism and argue that AI influencers holds similar values in society. The bulk of this paper will argue that AI influencers can be ethically designed and implemented because these influencers can adhere to the AI code of ethics and not pose a problem for larger philosophical issues such as machine consciousness and technological singularity. Finally, I will consider some implications of having ethically designed AI influencers in society, particularly unemployment and social stagnation, and explain how AI influencers will not pose much of a problem to these two implications.